MOLECULAR EVIDENCE OF PHOSPHOLIPASE A2 (PLA2) IN THE VENOM OF Loxosceles similis - Larangote, Débora; Kalapothakis, Yan; Miranda, Kelton; Kalapothakis, Evanguedes (Acta Biologica Brasiliensia, 2025)
Brown spiders of the genus Loxosceles (Araneae, Sicariidae) occur in both temperate and tropical regions around the world. Envenomation caused by their bites may progress to loxoscelism, a condition that the World Health Organization (WHO) classifies as a neglected public health problem. In Brazil, where medically relevant species are mainly distributed across the Southern and Southeastern regions, the number of reported accidents has been rising. Although Loxosceles similis is typically associated with subterranean habitats, it is also found in surface environments and has even been reported inside houses in Southeastern Brazil, suggesting a potential for endemicity. Caves, including those with tourist activity, present a particularly high likelihood of harboring this species, which may put visitors at risk. Most accidents occur when spiders hidden in clothing or shoes are pressed against the skin. The initial bite is generally painless, with discomfort and pain appearing only after 2–4 hours, contributing further to delays in seeking medical attention and initiating therapy. In this study, we analyzed the transcriptome of L. similis venom gland and identified a putative Phospholipase A2 (PLA2)-encoding sequence. To our knowledge, this is the first report of a PLA2-like transcript in Loxosceles species. The presence of this sequence suggests that L. similis venom may harbor additional enzymatic components beyond the well-characterized Loxtox family, potentially contributing to local tissue damage, inflammatory processes, and systemic manifestations of loxoscelism. These findings expand current knowledge of Loxosceles venom composition and open new perspectives for understanding the molecular mechanisms underlying envenomation.